A Liga dos Camponeses Pobres (LCP) e a luta pela terra no nordeste : contribuição ao estudo sobre o movimento camponês no Brasil - Silva, David Pimentel Oliveira (2014)
The expansion of the capitalist model and its relations in the countryside not only created an enriched and organized landlord class but also created a dispossessed peasantry that began to fight for their reproduction, rooted in the struggle for possession of land. This has materialized, in the contradictory and conflicting movement of class struggle, the territorial dispute between a historic agrarian ruling class, serving the globalized capital and a mass of poor proletarianized and / or landless peasants who raised the banner of struggle for land and for Agrarian Reform throughout Brazil. Out of this context, a process of formation and disintegration of peasants social movements such as the formation of the MST and its dissents is born, in the more recent history of the country. Inserted in this historical context of fragmentation, divergence and dissidence, A Liga dos Camponeses Pobres (LCP) is a social movement that emerged right after the conflict of Santa Elina farm in 1995, which became known as the "Massacre of Corumbiara", and caused us to yearn for the scientific research when we knew their combative proposal. In this perspective, this study aimed to delve into analyzes of the struggle for land in the current situation, with reference to the actions undertaken by the Liga dos Camponeses Pobres in the struggle for land in northeastern territories. Thus, through the study of the processes of formation and of spatialization of the LCP, it was possible to analyze their forms of organization for struggle, the territorial transformations built over the consolidation of the disputed territories and the major clashes on issues involving the struggle for land in the current situation. The historical dialectical materialist method allowed us to obtain the essence of the reality studied within the subject-object relationship, as well as the work with the theoretical clarity of class antagonisms. Through this method, it was possible to make a theoretical and methodological return to the geographical science, giving a contribution to the debate surrounding the concepts of Space, Territory and Peasant Movement.